Clinical value of metagenomic next-generation sequencing by Illumina and Nanopore for the detection of pathogens in bronchoalveolar lavage fluid in suspected community-acquired pneumonia patients - Zhang, Jing; Gao, Lin; Zhu, Chi; Jin, Jiajia; Song, Chao; Dong, Hang; Li, Zhenzhong; Wang, Zheng; Chen, Yubao; Yang, Zhenhua; Tan, Yan; Wang, Li (Frontiers in Cellular and Infection Microbiology, 2022)
At present, metagenomic next-generation sequencing (mNGS) based on Illumina platform has been widely reported for pathogen detection. There are few studies on the diagnosis of major pathogens and treatment regulation using mNGS based on Illumina versus Nanopore. We aim to evaluate the clinical value of metagenomic next-generation sequencing (mNGS) by Illumina and Nanopore for the detection of pathogens in bronchoalveolar lavage fluid (BALF) in suspected community-acquired pneumonia (CAP) patients. BALF samples collected from 66 suspected CAP patients within 48 hours of hospitalization were divided into two parts, one for conventional culture and the other for mNGS by two platforms (Illumina and Nanopore). The clinical value based on infection diagnosis, diagnostic performance for main pathogens and treatment guidance were assessed. More types of species were detected by Nanopore than Illumina, especially in viruses, fungus and mycobacterium. Illumina and Nanopore showed similar detectability in bacterium except for mycobacterium tuberculosis complex / nontuberculosis mycobacteria. Pathogenic infection was established or excluded in 53 of 66 patients. There was little difference in the coincidence rate between Illumina and Nanopore with the clinical diagnosis, but both were superior to the culture (57.81%, 59.38%, 25%, respectively). Compared with Illumina, the diagnostic area under the curve of Nanopore was higher in fungi, but lower in bacteria and Chlamydia psittaci. There was no statistically significant difference between Illumina and Nanopore in guiding drug treatment (56.1% vs. 50%, p=0.43), but both were superior to the culture (56.1% vs. 28.8%, p=0.01; 50% vs. 28.8%, p=0.01). Single inflammatory indicators could not be used to determine whether the patients with culture-negative BALF were established or excluded from infection. The species detected at 1 h and 4 h by Nanopore were consistent to some extent, and its turn-around time (TAT) was significantly shorter than Illumina (p<0.01). Illumina and Nanopore both have its own advantages in pathogenic diagnosis and play similar roles in infection diagnosis and guiding clinical treatment. Nanopore has a relatively short TAT, which may be promising in rapid etiological diagnosis of acute and critically ill patients.